Analysis of the Eco Enzyme Project in Fostering Environmental Literacy in Early Childhood - Irmawati, Irmawati; Nazihah , Nazihah (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The large amount of unprocessed waste in the school environment triggers an unpleasant odor in the school environment. This disrupts the learning process. Learning through real experience is more quickly understood by children. Early childhood students develop an understanding of environmental literacy by doing basic things such as sorting and disposing of waste and turning it into eco-enzymes which help reduce the negative impact of waste on the environment. The research aims to foster children's environmental literacy, apply the character of loving the environment, and children's understanding of the process of processing organic waste into eco enzymes. This research uses a qualitative approach, and data collection techniques using observation, interviews, and documentation. Checking the validity of the data uses source triangulation. The data analysis technique comes from Miles and Huberman through a process of data reduction, data presentation, and validation. The research results show that the eco enzyme project can foster children's environmental literacy skills. It can be seen that children can dispose of waste according to the color of the trash can, children can classify types of waste that are easily decomposed and suitable to be made into eco enzymes and children can process waste into fertilizer and pesticides to help reduce waste in the environment.